Multi-omics analysis of miRNA-mediated intestinal microflora changes in crucian carp Carassius auratus infected with Rahnella aquatilis - Huo, Jiaxin; Li, Xiaowei; Hu, Xiucai; Lv, Aijun (Frontiers in Immunology, 2024)
An emerging bacterial pathogen Rahnella aquatilis infection caused enteritis and septicemia in fish. However, it is still unclear on the molecular pathogenesis of enteritis induced by R. aquatilis infection, and its interacting mechanism of intestinal microflora associated with miRNAs immune regulation in crucian carp Carassius auratus. In this study, C. auratus with intraperitoneal injection of R. aquatilis KCL-5 was used as an experimental animal model, and the intestinal pathological changes, microflora as well as differentially expressed miRNAs (DEMs) were investigated by multi-omics analysis. The significant changes of histopathological features, apoptotic cells, and enzymes activities (eg., LYS, AKP, ALT, AST, GSH-Px) in intestine were examined after infection. Diversity and composition analysis of intestinal microflora clearly demonstrated four dominant bacteria including Proteobacteria, Fusobacteria, Bacteroidetes and Firmicutes, respectively. A total of 87 DEMs were significantly screened, and KEGG enrichment analyses revealed that the potential target genes were mainly involved in the regulation of lipid, glutathione, cytosine and purine metabolism, which participated in the local immune response through the intestinal immune network for IgA production, lysosome and TLR pathways. Moreover, the expression level of eleven target genes (eg., TLR3, MyD88, NF-κB, TGF-β, TNF-α, MHC Ⅱ, IL-22, LysC, F2, F5, C3) related to inflammation and immunity were verified by qRT-PCR detection. The correlation analysis indicated that the abundance of intestinal Firmicutes and Proteobacteria was significantly associated with the high local expression of miR-203/NF-κB, miR-129/TNF-α and miR-205/TGF-β, respectively. These findings will help to elucidate the molecular regulation mechanism of intestinal microflora, inflammation, and immune response-mediated miRNA-target genes axis in cyprinid fish.